Yoga Batu-Q: Game Edukasi Kearifan Lokal Temanggung Pembelajaran Tajwid Waqaf Washal Kelas 5 SD/MI - Yoga Dwi Prada; Muhammad Fadloli Al Hakim; Hamidulloh Ibda (Balai Diklat Keagamaan Semarang, 2025)
The lack of development of educational games with local wisdom in learning Al-Quran tajweed material, especially the reading laws of waqof and washal for grade 5 SD / MI students. This research aims to analyze the needs of students and teachers for the development of the Batu-Q game, and test the feasibility of the Batu-Q game with Temanggung local wisdom. The type of Research and Development (RnD) with ADDIE method type Robert Maribe Branch. This research was conducted at 34 MI / SD, and 1 MI as a limited scale trial. The data collection technique used a needs analysis questionnaire, feasibility test questionnaire, and document study. Data analysis techniques were carried out using quantitative and qualitative interpretative analysis techniques. The research findings state that the development of the Batu-Q game was carried out with ADDIE stages which obtained a game with an attractive profile for learning Al-Quran in the aspects of waqof and washal in grade 5 SD / MI. The results of the needs of Batu-Q game development from the student element get a score of 85.20%, and the teacher element gets a score of 83.20% which means it is in great need. The game feasibility test results from game media experts get a score of 97.5%, the test results of local wisdom material experts get a score of 90%, and from Al-Quran material experts get a score of 90% which shows the Batu-Q game is feasible to implement. This research is limited to the Batu-Q game for grade 5 SD / MI, and is limited only to waqof and washal reading material. Future research needs to be done to develop more innovative educational games to answer the challenges of the times.